2021
DOI: 10.1002/mds.28577
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol for Rapid Eye Movement Sleep Behavior Disorder

Abstract: Background: REM sleep behaviour disorder (RBD) is a common non-motor feature of Parkinson's disease (PD). Cannabidiol (CBD) is one of the main non-psychoactive components of Cannabis sativa and may represent an alternative route for treating RBD.Objective: This study assessed the efficacy and safety of CBD for RBD in PD. Methods: We conducted a phase II/III, double-blind, placebo-controlled clinical trial in 33 patients with RBD and PD. Patients were randomized 1:1 to CBD in doses of 75 to 300mg or matched cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 30 publications
0
25
0
1
Order By: Relevance
“…Results of randomized clinical trials, most of them involving a limited number of patients, have shown the short-term efficacy of the anticholinesterase drugs rivastigmine [67,68] and 5-hydroxytryptophan [75] and the herbal medicine yokukansan [81,82], as well as the lack of efficacy of nelotanserin [74] and cannabidiol [79]. Memantine has shown some degree of medium-term efficacy in the reduction of RBD symptoms in patients with LBD and dementia associated with PD [83].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of randomized clinical trials, most of them involving a limited number of patients, have shown the short-term efficacy of the anticholinesterase drugs rivastigmine [67,68] and 5-hydroxytryptophan [75] and the herbal medicine yokukansan [81,82], as well as the lack of efficacy of nelotanserin [74] and cannabidiol [79]. Memantine has shown some degree of medium-term efficacy in the reduction of RBD symptoms in patients with LBD and dementia associated with PD [83].…”
Section: Discussionmentioning
confidence: 99%
“…Cannabidiol is a phytocannabinoid that acts an antagonist of the cannabinoid CB 1 and CB 2 receptors, with a low affinity for them. Following the description of short-term improvements of RBD symptoms in four patients with PD and RBD [78], a randomized placebo-controlled clinical trial involving 33 patients with PD and RBD (level I of evidence; quality score >50%) showed improvement in sleep satisfaction but not significant differences in the control of RBD at two different doses of cannabidiol compared with placebo [79].…”
Section: Cannabinoidsmentioning
confidence: 99%
“…Among those, there were seven double-blinded randomised trial results available. Three of the seven assessed the effect of pure CBD on PD symptoms [16][17][18], one study involved treatment with THC and CBD in combination [19], and two papers summarised the results of randomised clinical trials with nabilone [20,21]. Table 1 summarises the findings from the randomised studies.…”
Section: Resultsmentioning
confidence: 99%
“…The authors reported better sleep satisfaction at the 4 th and 8 th weeks in the CBD versus a placebo group with p = 0.049 and p = 0.038 respectively. This effect was, however, transient [16]. Leehey et al [22] also reported improvements in sleep, reflected by SCOPA-sleep change, but no effect of treatment with CBD on RBD.…”
Section: Non-motor Symptoms Of Pd Sleepmentioning
confidence: 97%
“…A subsequent 12-week randomised placebo-controlled trial of CBD for RBD in Parkinson’s disease found it no better than placebo for treating RBD symptoms. 60 De Almeida et al carefully characterised patients with RBD, confirmed the diagnosis by loss of REM atonia and ensured the 33 participants included had a bed partner to monitor RBD activity, which was the primary outcome measure. Participants were randomised to placebo (n = 16) or 75mg to 300mg CBD (n = 17) daily oral capsules, taken in the evening.…”
Section: Effect Of Mixed Cannabinoid Formulations On Insomniamentioning
confidence: 99%